Selective Electroreduction of Carbon Dioxide to Formic Acid on Cobalt‐Decorated Copper Thin Films. Issue 11 (7th June 2019) - Dai, Chencheng; Sun, Libo; Song, Jiajia; Liao, Hanbin; Fisher, Adrian C.; Xu, Zhichuan J.
Abstract: The development of highly efficient, selective, and economic approaches for electrochemical reduction of carbon dioxide to hydrocarbons is a promising way to promote the sustainable carbon cycle nowadays. Here, a stable cobalt‐decorated copper catalyst is reported with significantly enhanced selectivity toward formic acid produced from CO2 through electrochemical reduction. This catalyst is prepared through the electrodeposition of cobalt on the surface of copper, followed by Ar and air atmosphere treatment. The as‐prepared catalyst exhibits selective conversion of CO2 to formic acid with a Faradaic efficiency (FE) of ≈80% at an applied potential of −0.65 V versus reversible hydrogen electrode. Meanwhile, the copper electrode treated with the same conditions without cobalt decoration and the cobalt‐decorated copper electrode without Ar treatment process only show an FE toward formic acid of ≈56% and ≈57% from CO2 reduction, respectively. This study represents a facile decoration method to prepare highly selective electrocatalysts for the efficient reduction of CO2 to value‐added chemicals in aqueous electrolytes. Abstract : A cobalt‐decorated copper thin film is prepared through the electrodeposition of cobalt on the surface of copper, followed by Ar and air atmosphere treatment. The cobalt‐decorated copper electrode exhibits selective conversion of CO2 to formic acid with an optimal Faradaic efficiency of ≈80% at an applied potential of −0.65 V versus reversible hydrogen electrode in CO2 ‐saturated 0.1 m KHCO3 .